Quality of Water and the Recovery Time of Malnourished Children Enrolled In a Nutritional Feeding Programme: Lessons from Parkishon Region, Marsabit County, Kenya - Kirira, Peter G.; Cheren, Connie; Ndegwa, Linus; Waudo, Ashley (Archives of Clinical and Medical Case Reports, 2018)
Objective: Malnutrition is a problem that continues to plague children from resource scarce regions of Kenya. To address this health challenge, the government of Kenya initiated feeding programmes aimed at improving the daily nutritional food intake of underweight and sickly children from these regions. This study examined the relationship between the quality of water and the children’s recovery as measured by the Mid-Upper Arm Circumference (MUAC) in Parkishon region of Kenya. Methods: The study followed 82 underweight children on a PlumpNut diet. Thirty seven (37) children were using water from a water backpack while the other children were using water from Silanga, a dam that is the only source of water in the region. The recovery time of the children was measured using the MUAC index. Results: Of the 37 children enrolled in the nutritional feeding programme and from families that received the water backpack, 10 recovered fully within three months and were put off the nutritional supplement program. The underweight children in the same nutritional feeding programme but whose families did not receive the water backpack, and therefore continued to consume water from the dam, are yet to recover and are still enrolled in the nutritional feeding programme. Conclusion: The study showed that the children nutritional feeding programmes should put into consideration the quality of water since it affects the recovery time of children enrolled in the nutritional programme. This study demonstrated the significant role of the water backpack in improving the health conditions of the children.